Proton beam therapy reduces the risk of severe radiation-induced lymphopenia during chemoradiotherapy for locally advanced non-small cell lung cancer: A comparative analysis of proton versus photon therapy. (March 2021) - Kim, Nalee; Myoung Noh, Jae; Lee, Woojin; Park, Byoungsuk; Park, Heejoo; Young Park, Ji; Pyo, Hongryull
Highlights: Pencil beam scanning proton therapy reduced the risk of SRL by the reduced irradiated lung volume. Lung V5, baseline absolute lymphocyte counts, and planning target volume contributed to SRL. Severe radiation-induced lymphopenia (SRL) was related to poor outcomes in NSCLC. Abstract: Hypothesis: We investigated differences in severe radiation-induced lymphopenia (SRL) after pencil beam scanning proton therapy (PBSPT) or intensity-modulated (photon) radiotherapy (IMRT) for patients with locally advanced non-small cell lung cancer. Methods: We retrospectively reviewed 223 patients who received definitive concurrent chemoradiotherapy with PBSPT ( n  = 29) or IMRT ( n  = 194). SRL was defined when ≥2 events of absolute lymphocyte counts (ALCs) of <200 cells/μL were observed in weekly laboratory tests conducted during treatment. Stepwise multivariate logistic regression with 10-fold cross-validation was performed to identify predictive values of SRL. Furthermore, 1:2 propensity score matching (PSM) analysis was performed between the PBSPT and IMRT groups. Results: Baseline ALC was comparable between the PBSPT and IMRT groups (median, 2130 vs. 2040 cells/μL; p  = 0.983). Lung volumes receiving ≥ 5–20 GyE and the mean dose were significantly lower in patients receiving PBSPT than those receiving IMRT ( p  < 0.001). Among 72 (32.3%) patients with SRL; 69 (95.8%) and 3 (4.2%) patients were treated with IMRT and PBSPT, respectively. After multivariable analysis, PBSPT reduced SRL compared to IMRT (odds ratio [OR] 0.13, p  = 0.003). Specifically, lung V5Gy were identified as the strongest predictor of SRL before (OR 1.11) and after PSM (OR, 1.07) ( p  < 0.05). With a median follow-up of 23.0 months, the 2-year overall survival in patients with SRL was worse than that those without SRL (63.4% vs. 79.9%; p  = 0.003). Conclusions: Reduced irradiated lung volumes of PBSPT consequently reduced SRL. In addition, lung V5Gy contributed to the SRL. Reduction of SRL through the optimized RT might be essential to improve the outcomes.